Hennobrimus hennemanni n. gen. n. sp., a remarkable new genus and species of the tribe Obrimini from the Philippine Islands (Phasmatodea: Heteropterygidae: Obriminae: Obrimini) - Conle, Oskar V. (Zootaxa, 2006)
A new genus and species (Hennobrimus hennemanni n. gen. n. sp.) of the tribe Obrimini from the Philippine Islands of Mindanao and Leyte are described and illustrated from both sexes. The holotype is preserved in the State Zoological Collections Munich, Germany (ZSMC). Paratypes are deposited in the private collection of the author (OC) and in the private collection of Frank H. Hennemann (Kaiserslautern, Germany; FH).